Analisis Kemampuan Komunikasi Matematis pada Materi Persegi dan Persegi Panjang untuk Siswa - Zaghu, Lazarus Andrianus Pati; Lede, Yulius Keremata; Kii, Wilhelmus Yape (CT. Rajawali media Utama, 2023)
This article examines the level of students' numeracy literacy skills. The reference in testing students' numeracy literacy skills in this study used math questions in the PISA program for students aged 15 years. The ranking of Indonesian students' mathematical literacy from 2009 to 2015 did not show a significant increase. In 2009 Indonesia was ranked 68th out of 74 countries. In 2012 Indonesia ranked 64th out of 65 countries with a relatively low level of achievement. While the results of PISA in 2015 showed that Indonesia's ranking experienced a slight increase, namely 63rd out of 72 countries. The purpose of writing this article is to find out how far the students' numeracy literacy skills are at SMP Negeri 3 Tambolaka City. The method used is a type of sequential explanatory research and a mixed method research approach.